2008
DOI: 10.1248/jhs.54.23
|View full text |Cite
|
Sign up to set email alerts
|

Present State of New Chiral Drug Development and Review in Japan

Abstract: The current situation of chiral drug development in Japan was investigated. The trend in the Japanese pharmaceutical development is increasingly moving towards the development of single isomers rather than racemates. The development of single-enantiomer drugs was made possible by the current technologies of asymmetric synthesis and chiral separation, and encouraged by the guidelines on the development of chiral drugs worldwide. Japan has not issued specific guidelines on the development of chiral drugs, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 5 publications
0
41
0
1
Order By: Relevance
“…Enantioselective identification and quantification methods should be developed for each active pharmaceutical ingredient with chiral properties. In addition pharmacokinetic and toxicological assays should be executed with both pure enantiomers and with the racemate [8][9][10][11]. These requirements made chiral separations a well-recognized and extensively studied topic in today's drug development [7].…”
Section: Introductionmentioning
confidence: 99%
“…Enantioselective identification and quantification methods should be developed for each active pharmaceutical ingredient with chiral properties. In addition pharmacokinetic and toxicological assays should be executed with both pure enantiomers and with the racemate [8][9][10][11]. These requirements made chiral separations a well-recognized and extensively studied topic in today's drug development [7].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] This trend emerged as a result of increasing awareness of individual biological properties for opposite enantiomers in racemic drugs. [5][6][7][8] Two approaches can be used to produce single enantiomers, which involve either resolution of racemates or stereoselective synthesis from achiral material.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of these compounds with a particular stereochemistry presents a challenge to chemists as well as to health specialists. Currently, a high fraction of the active principles of pharmaceutical drugs is commercialized as racemates [1][2][3] . Nevertheless, in the last decade there has been a substantial increment in the distribution of enantiomerically pure substances 1 , as it has been shown that there is usually a pharmacokinetic and pharmacodynamic advantage of using only one enantiomer (eutomer) over the other (distomer) [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a high fraction of the active principles of pharmaceutical drugs is commercialized as racemates [1][2][3] . Nevertheless, in the last decade there has been a substantial increment in the distribution of enantiomerically pure substances 1 , as it has been shown that there is usually a pharmacokinetic and pharmacodynamic advantage of using only one enantiomer (eutomer) over the other (distomer) [4][5][6] . On the other hand, the distomer may have a different kind of biological activity, even toxicity 5,7 , or it may have the same activity but different affinity to the receptor.…”
Section: Introductionmentioning
confidence: 99%